Factors affecting service delivery within community pharmacy in the United Kingdom - Thornley, Tracey (2006)
Aims of study The overall aim of this study was to investigate factors affecting service delivery within a national pharmacy chain, from the perspective of pharmacists and consumers, using asthma services as an example. Data were collected to explore the current environment and opportunities available to pharmacy, the factors affecting service delivery, and to identify recommendations for future service models. The impact of the design and route of service implementation were studied through two different types of asthma services.